Autoeficácia em amamentação de puérperas em alojamento conjunto: contribuições para o cuidado de enfermagem - Rodrigues, Andressa Peripolli (2013)
It was aimed to evaluate self-efficiency in breastfeeding of women in puerperium admitted in joint accommodation and to verify socio-demographic and obstetric factors associated to selfefficiency. It is a cross-sectional study of quantitative approach, developed with 322 women in puerperium of a University Hospital in the South of Brazil. Data collection occurred from December 2011 to March 2012, using the Breastfeeding Self-Efficacy Scale Short Form and characterization form to characterize the women. Data were analyzed statistically on then software Statistical Package for Social Science (SPSS, version 17.0). Age average of pregnant women was of 26,4 years old, single (66,15%), low schooling (35,71%), average monthly income 1,9 minimum wage and didn t work (67,08%). A great part had breastfeeding previous experience (91,59%) and 66,46% was multiparous. Women in puerperium also developed prenatal care (95,96%), being that part of them had cesarean section (63,66%) and early contact with the baby after delivery (82,92%). Accordingly to self-efficiency, most women in puerperium (81,06%) presented high self-efficiency on breastfeeding. Through bivariate analysis, it was possible to identify meaningful statistics association of selfefficiency on breastfeeding with the fact of the woman in puerperium not using drugs (p=0,035), having breastfed previously (p=0,026), exclusive breastfeeding (p=0,012), liking to breastfeed (p=<0,001) and having put the baby to suck after the first hour of delivery (p=0,018). Thus, on evaluating self-efficiency on breastfeeding, nursing professionals will have subsides to support breastfeeding practice, in order to promote greater confidence and security to the woman.